2015
DOI: 10.4238/2015.august.21.6
|View full text |Cite
|
Sign up to set email alerts
|

Short Communication Thymidylate synthase and methylenetetrahy­drofolate reductase gene polymorphisms and gastric cancer susceptibility in a population of Northern Brazil

Abstract: ABSTRACT. The folate metabolic pathway, which is involved in DNA synthesis and methylation, is associated with individual susceptibility to several diseases, including gastric tumors. In this study, we investigated four polymorphisms [thymidylate synthase enhancer region, single nucleotide polymorphism thymidylate synthase 5' (TS5'), TS3' untranslated region, and methylenetetrahydrofolate reductase (MTHFR) 677C> T] in 2 genes related to the folate pathway, TS and MTHFR, and their possible association with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Shen et al [40] found that the del6/del6 genotype of TS 3′-UTR was associated with significantly increased gastric cancer risk, Sumen et al [41] suggested that 3R allele, 2R/3R and 3R/3R genotypes were risk factors for gastric cancer, whereas Araújo et al [55] did not obtain a significant relationship between TS 5′-UTR 2R/3R and 3′-UTR del6/ins6 polymorphisms and gastric cancer susceptibility. Studies have also shown that TS polymorphisms might be associated with other cancers’ risks such as colon cancer [56], lung cancer [57] and oral squamous cell carcinoma [58].…”
Section: Discussionmentioning
confidence: 99%
“…Shen et al [40] found that the del6/del6 genotype of TS 3′-UTR was associated with significantly increased gastric cancer risk, Sumen et al [41] suggested that 3R allele, 2R/3R and 3R/3R genotypes were risk factors for gastric cancer, whereas Araújo et al [55] did not obtain a significant relationship between TS 5′-UTR 2R/3R and 3′-UTR del6/ins6 polymorphisms and gastric cancer susceptibility. Studies have also shown that TS polymorphisms might be associated with other cancers’ risks such as colon cancer [56], lung cancer [57] and oral squamous cell carcinoma [58].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies show that the 677 and 1298 polymorphisms could be a risk factor for different type of cancer (ARAUJO et al 2015, AL-MOTASSEM et al 2015, and could also influence the radiotherapy treatments in patients with head and neck squamous cell carcinoma, presumably through the role of MTHFR in DNA methylation (FRISO et al 2012, JONES 2015, ANDERS et al 2015.…”
Section: Discussionmentioning
confidence: 99%
“…The focus of many studies since 1995 has been the association between the 677 C>T polymorphism, plasma homocysteine concentrations, and various clinical conditions: cardiovascular diseases-CVD (FROSST et al 1995, CHRISTENSEN et al 1997, SAFFARI et al 2013, HANSON et al 2001, vein thrombosis (DJORDJEVIC et al 2011), and neural tube closure defects (VAN DER PUT et al 1998, BEAUDIN andSTOVER, 2009). More recently, the findings that individuals homozygous for 677TT exhibit lower levels of genomic DNA methylation under low folate status (FRISO et al 2012) and that global DNA hypomethylation is observed in early tumorogenesis (JONES 2005), suggested that the 677 C>T mutation could also be connected with the development of cancer (ARAUJO et al 2015, AL-MOTASSEM et al 2015.…”
Section: Introductionmentioning
confidence: 99%
“…However, no association has been established between the TYMS 5'-UTR VNTR polymorphism and the incidence of gastric tumors, breast cancer, or leukemia (Nazki et al, 2012;Quintero-Ramos et al, 2014;Araújo et al, 2015).…”
Section: Discussionmentioning
confidence: 99%